Adopsi Teknologi Informasi sebagai Literasi Digital Masa Pandemi Covid-19 bagi Para Perempuan di Pedesaan - Ratna Susanti; Nilam Astari Putri (Neolectura, 2022)
Technology was created to make it easier for humans, but its use also requires user skills. The rapid flow of information and the occurrence of digital transformation are part of the result of disinformation circulating in the community. During the Covid-19 pandemic, many hoax issues were spread on various digital platforms. Digital literacy is very important to accompany the rapid development of technology. This study aims to identify the access to information through digital technology for rural communities living in the Klaten area during the Covid-19 pandemic. The methods for collecting data were surveys and interviews with informants, namely people who live in rural areas of Klaten and have children attending primary school level. The results of the barriers to internet users were obtained viii because: (1) they did not know how to use technology, (2) they were not interested or did not feel the need to use it because they did not know the function of the internet, and (3) the high cost of the internet. In addition, it was found that there was a digital divide between members of the rural community in the Klaten area who were less fortunate, especially those living below the poverty line, the elderly, and even people with disabilities. The conclusion is that the digital divide is influenced by age, education level, and income level. The older a person is, the lower the level of education and income, the smaller the chances of adopting the use of information technology as digital literacy.